2015
DOI: 10.1016/j.jff.2014.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Potato protein hydrolysate attenuates high fat diet-induced cardiac apoptosis through SIRT1/ PGC-1á/Akt signalling

Abstract: Available online A B S T R A C THigh-fat-diet (HFD)-induced obesity is a major contributor to diabetes and cardiovascular disease. In this research 6 week old male hamsters (n = 10) fed with HFD showed significant deterioration in heart function as determined from their cardiac ejection fraction percentage (EF%) and fraction shortening percentage (FS%). The number of apoptosis positive cells and the expression of protein markers of apoptosis drastically increased in the HFD-fed hamsters. However, the effects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…In this study, the C57/BL6 mice showed increase in the IGF‐1R survival mechanism as a compensative protective mechanism against HFD and andrographolide treatment further upregulated the IGF‐1R survival mechanism and fortified the cardio‐protection in obese mice (Figure ). Furthermore, our previous studies on obesity and diabetes in Zuker rats, SD rats, C57/BL6 mice and in hamsters showed a common set of changes in cardiac tissue morphology such as cardiac tissue disarray, increased interstitial space, and minor cardiac fibrosis, and further displayed significantly increased protein levels of Fas ligand, Fas death receptors, and FADD . In this study, HFD feeding in C57/BL6 mice triggered increase in the number of TUNEL‐positive apoptotic cells in heart and further caused minor cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 58%
“…In this study, the C57/BL6 mice showed increase in the IGF‐1R survival mechanism as a compensative protective mechanism against HFD and andrographolide treatment further upregulated the IGF‐1R survival mechanism and fortified the cardio‐protection in obese mice (Figure ). Furthermore, our previous studies on obesity and diabetes in Zuker rats, SD rats, C57/BL6 mice and in hamsters showed a common set of changes in cardiac tissue morphology such as cardiac tissue disarray, increased interstitial space, and minor cardiac fibrosis, and further displayed significantly increased protein levels of Fas ligand, Fas death receptors, and FADD . In this study, HFD feeding in C57/BL6 mice triggered increase in the number of TUNEL‐positive apoptotic cells in heart and further caused minor cardiac fibrosis.…”
Section: Discussionsupporting
confidence: 58%
“…In addition to controlling the cardiac‐apoptosis, promoting the cell survival mechanism such as those involving insulin‐like growth factor‐I (IGF‐I) signaling pathways, mitogen‐activated protein kinases (MAPK)/extracellular signal‐regulated kinases (ERK) and phosphatidylinositol 3′‐kinase (PI3K)‐protein kinase B (Akt) is an important strategy in treating DM related cardiac‐dysfunction. Various alternative medicines with such potential are been extensively studied and reported …”
Section: Introductionmentioning
confidence: 99%
“…The use of low grade sources as starting material for the generation of peptides with bioactive activity is increasingly popular . Specifically, several studies have highlighted the beneficial properties of potato protein hydrolysates including their participation in angiotensin converting enzyme inhibition, their antioxidant potential, their lipolysis‐stimulating activity, and their effect on serum cholesterol levels . Most of these studies have primarily used one protease, Alcalase, and have evaluated the degree of hydrolysis based on free amino acids and not on the generated peptides.…”
Section: Introductionmentioning
confidence: 99%